DETERMINATION OF PRODUCED AND CONSUMED ELECTRICITY OF A RESIDENTIAL BUILDING USING A GRAPHICAL USER INTERFACE - Sredenšek, Klemen; Simonič, Eva; Brinovar, Iztok; Seme, Sebastijan (Journal of Energy Technology, 2023)
The primary objective of this paper is to present a graphical user interface for the calculation of electricity produced by a photovoltaic system and electricity consumed by a heat pump. The produced electricity is determined by a multi-year average of measurements of the global and diffuse power density of solar radiation for several places in Slovenia, while consumed electricity is determined based on the required heat for heating a residential building and domestic water. The calculation of produced and consumed electricity is validated by measurements on a real system. The developed graphical user interface enables simple user inputs of the photovoltaic system, heat pump, and the considered residential building, and provides a comprehensive tech-nical analysis for installing both systems at the same location.